Website-Based Learning Management System (LMS) as a Tool for Learning in the Covid-19 Pandemic Period for Junior High Schools - Sumardi, Dody; Suryani, Nunuk; Musadad, Akhmad Arif (Universitas Pendidikan Ganesha, 2021)
The availability of facilities has not been able to optimize the implementation of learning. This has resulted in some students not being able to take online lessons properly; about 29.4% of students have never taken online lessons so that students miss lessons that are carried out according to schedule. This study aims to develop a website-based Learning Management System to facilitate learning during the covid-19 pandemic. This research is included in research and development (R&D) by adopting the Alessi & Trollip development model. The subjects of this study were, among others, two media experts, two material experts, and two subject teachers in junior high schools. The data collection technique used a test based on the product developed for each research subject using the appropriate instrument. The results of the questionnaire will be analyzed descriptively using the proportion to choose the LMS product. The results of the research data that the assessment above is 88.88% of media experts, the amount of material obtained is 91.22%, and prospective users consisting of students and teachers are 91.88%, which means that the acquisition of media and subject matter to be used is 81%, which are included in the very decent or excellent category so that there is no need for revision or improvement. Thus the learning application, namely the learning management system (LMS), can be used as a tool to support the learning process during online learning activities.